تأثير نوع السماد العضوي والسماد الحيوي في بعض الصفات المورفولوجية والفيزيولوجية لنبات الكزبرة(Coriandrum sativum L) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
The lack of information on the cultivation of coriander in Syria has reinforced the importance of this study, which examined the effect of three types of organic fertilizers (Cattle manuer, compost, chicken-manuer)  at a rate of 15 tons / ha each, and four levels of EM1 fertilizer (0, 0.5, 1 and 1.5 ml) As paper feed and liters / dan as a radical feed. On some morphological traits of coriander. This study was conducted in the city of Banias Huraisoun area during the agricultural season 2018 using the design of the complete random sectors in accordance with the order of splitting pieces twice for the studied transactions. The results showed that there were statistically significant differences between the coefficients for most of the studied traits. In addition, there was a mutual effect between organic fertilization and bio-fertilization concentrations. Although concentrations (0.5, 1, 1.5 ml) varied in effect, The concentration of 1.5 L/dunum was significant in terms of increasing the number of branches / plants, number of leaves / plants. On the other hand, organic fertilization has exceeded the chemical in all the attributes: number of shoots / plant, number of leaves / plant, and plant height. While chemical fertilization had a significant effect on the chlorophyll content (A, B, T). عزّزت قلّة المعلومات حول زراعة نبات الكزبرة في سوريا أهمية هذا البحث الذي تناول دراسة تأثير ثلاث أنواع من التسميد العضوي (سماد بقري، كومبوست، سماد دواجن) بمعدل 15طن/هكتار لكل منهم، وأربعة مستويات من المخصب الحيوي EM1 (0، 0.5، 1 و1.5) مل/ل كتغذية ورقية ولتر/الدنم كتغذية جذرية. على بعض الصفات المورفولوجية لنبات الكزبرة. أجريت هذه الدراسة في مدينة بانياس منطقة حريصون خلال الموسم الزراعي 2018 باستخدام تصميم القطاعات العشوائية الكاملة وفق ترتيب القطع المنشقة مرتين للمعاملات المدروسة. أظهرت النتائج أن هناك فروقاً معنوية ذات دلالة إحصائية بين المعاملات بالنسبة لمعظم الصفات المدروسة، بالإضافة إلى وجود تأثير متبادل بين التسميد العضوي وتراكيز المخصب الحيوي، وعلى الرغم من أن التراكيز (0.5, 1, 1.5 مل/ل) تفاوتت في تأثيرها، إلا أنها تفوقت معنوياً على الشاهد، وكان التركيز1.5ل/الدونم أهميةً من حيث زيادة كل من: عدد الأفرع/النبات، ، عدد الأوراق/النبات. من ناحية أخرى، فقد تفوق التسميد العضوي على الكيميائي في جميع الصفات: عدد النورات/نبات، عدد الأوراق /نبات، وارتفاع النبات. في حين كان للتسميد الكيميائي أثر معنوي في محتوى الكلوروفيل (A,B,T).